Proactive model based testing and evaluation for component-based systems - Surendar, A.; Kavitha, M.; Saravanakumar, V. (International Journal of Engineering and Technology, 2017)
Embedded software systems are getting more and more complex. The demand for new features and functions led to an increasing complexity in the design and development of these systems. There are frequent reports in the media about software systems crashing and damages occurring due to software errors. One reason for this is that there are many software testing methods and techniques but they are often non-practical and difficult to use. The aim of the study was to improve existing testing methods and their practicality especially from the integrator viewpoint. Component-based system development, components of different granularities must be tested. Furthermore, an optimization approach based on simulated annealing is presented which is used to derive an integration order with respect to the proposed parameters in a powerful and reliable manner. The paper discusses explicit properties and the requirements that are to be verified, imposed upon software-intensive systems by their environment and by their users.